ANTESEDEN DAN KONSEKUENSI KEPUASAN KONSUMEN SERTA PERAN MEDIASI SIKAP TERHADAP MEREK PADA LOYALITAS DALAM LAYANAN SHOPEE - Dwi Puspa Maharani Usali Rachman; Zunan Setiawan; Sukardi Sukardi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study investigates the impact of social media marketing elements, namely entertainment, customization, interaction, electronic word of mouth and trends, on consumer engagement on brands and brand knowledge. This study collects Research conducted using an online survey distributed to 273 respondents by distributing questionnaires and meeting the criteria of respondents who are Shopee service users. Overall, the sample profile broadly matches the research objective, namely shopee service users in representatives of major cities in Indonesia based on a 5-point Likert scale, using measurement items adopted from the Smith study (2020). This analysis presents a partial least squares structural equation modeling (PLS–SEM) using SmartPLS v3.2.8.